Respuesta :
Answer:
- 24
Step-by-step explanation:
y is directly proportional to the square root of ( x-3):
- y = k[tex]\sqrt{x-3}[/tex], where k is the coefficient of proportionality
Given:
- y is 20 when x is 28
Find k:
- 20 = k[tex]\sqrt{28-3}[/tex]
- 20 = k* 5
- k = 20/5
- k = 4
Find y when x = 39:
- y = 4[tex]\sqrt{39-3}[/tex]
- y =4[tex]\sqrt{36}[/tex]
- y = 4*6
- y = 24
Answer:
y = 24
Step-by-step explanation:
Given y is directly proportional to [tex]\sqrt{x-3}[/tex] then the equation relating them is
y = k[tex]\sqrt{x-3}[/tex] ← k is the constant of proportion
To find k use the condition when x = 28, y = 20 , then
20 = k × [tex]\sqrt{28-3}[/tex] = k × [tex]\sqrt{25}[/tex] = 5k ( divide both sides by 5 )
4 = k
y = 4 [tex]\sqrt{x-3}[/tex] ← equation of proportion
When x = 39 , then
y = 4 × [tex]\sqrt{39-3}[/tex] = 4 × [tex]\sqrt{36}[/tex] = 4 × 6 = 24